Effect of Aflibercept on Cystoid Macular Edema Associated with Central Retinal Vein Occlusion. Results from a District Hospital in the United Kingdom - Panos, Georgios D.; Kostakis, Vassileios T.; Porter, Grazyna M. (Klinische Monatsblätter für Augenheilkunde, 2019)
Purpose The purpose of this study was to report the efficiency and safety of intravitreal aflibercept for the treatment of cystoid macular edema (CME) secondary to central retinal vein occlusion (CRVO).Methods This is a retrospective cohort study. Ten naive eyes of ten patients with CME secondary to CRVO were included. All eyes received a loading dose of 3 monthly aflibercept injections followed by as-needed injections at monthly follow-up visits. Best corrected visual acuity (BCVA) and central retinal thickness (CRT) were evaluated at baseline and at the end of the follow-up period.Results The median follow-up period was 6 months (range: 6 – 9). The median number of injections was 4 (range: 3 – 5). Median BCVA improved from 1.05 LogMAR units (range: 0.7 – 1.6) at baseline to 0.65 (range: 0.4 – 1.6) at the end of the follow-up period (p = 0.02). Median CRT improved from 690 µm (range: 561 – 1235) at baseline to 243 µm (range: 207 – 531) at the end of the follow-up period (p = 0.002). The power of all statistical tests was greater than 0.8. No adverse effects or complications were documented.Conclusion Intravitreal aflibercept treatment for CME secondary to CRVO significantly improved both macular anatomy and visual acuity without adverse effects.
Keywords: central retinal vein occlusion; aflibercept; Eylea; anti-VEGF; intravitreal injections; macular edema